UANG KRYPTO DALAM TRANSAKSI KONVENSIONAL DAN DIGITAL: Krypto Money In Conventional and Digital Transactions - Andi Widiatno Hummerson; Olivia Pauline Hartanti (Faculty of Law, Trisakti University, 2023)
This causes residents' activities to stop and impacted on the economy. For those whose wages have been reduced or lost their jobs. E-commerce offers a solution to becoming an investor in the digital crypto market. The crypto digital market uses cryptocurrencies or cryptocurrencies such as Bitcoin. There are several ways to convert a country's currency into cryptocurrency via the P2P method. Banks also have an important role in transferring money between accounts, but the legality of cryptocurrencies must be regulated and supervised by the OJK and BI. This is an effort for Indonesia to develop and compete with other developed countries. The problems in this paper are (1) What is the legality of bank transactions regarding the conversion of conventional currency into crypto currency? and (2) How do OJK and BI regulate transactions and use of crypto currency in Indonesia? The conclusions are (1) The legality of Bank transactions regarding the conversion of conventional currency into crypto currency for Bank transactions is of course guaranteed legal certainty because this has been regulated in the Fund Transfer Law. (2) There are still no regulations regarding transactions and use of crypto currency. The recommendation is that regarding buying and selling transactions using crypto money, new arrangements can be made similar to share buying and selling transactions that occur in the capital market